Temporal and Spatial Variations in Particle Fluxes on the Chukchi Sea and East Siberian Sea Slopes From 2017 to 2018 - Kim, Ho-Jung; Kim, Hyung Jeek; Yang, Eun-Jin; Cho, Kyoung-Ho; Jung, Jinyoung; Kang, Sung-Ho; Lee, Kyung-Eun; Cho, Sosul; Kim, Dongseon; , on behalf of the Collaborative Working Group (Frontiers in Marine Science, 2021)
Time-series sediment traps were deployed on the Chukchi Sea and East Siberian Sea slopes from August 2017 to August 2018 with the aim of elucidating the temporal and spatial variations in particle fluxes and identifying the main processes affecting those variations. Particle fluxes showed a typical seasonal pattern, with high values in summer and low values in other seasons, and a large inter-annual variation was observed only on the East Siberian Sea slope, where particle fluxes were one order of magnitude higher in early August 2018 than in late August 2017. This large inter-annual variation in particle flux resulted from the episodic intrusion of nutrient-enriched shelf water in the East Siberian Sea, which enhanced biological production at the surface and particle fluxes. The Chukchi Sea slope was influenced by the inflow of Anadyr Water, with high salinity and high nutrient concentrations, which had little annual variability. Therefore, particle flux showed little inter-annual variation on the Chukchi Sea slope. Under-ice phytoplankton blooms were observed in both the Chukchi Sea and East Siberian Sea slopes, and increases in particulate organic carbon (POC) flux and the C:N ratio under the sea ice were related to transparent exopolymer production by ice algae. On the East Siberian Sea slope, particle fluxes increased slightly from 115 m to 335 m, indicating lateral transport of suspended particulate matter; POC and lithogenic particles may be laterally transported to the slope as nutrient-rich shelf waters flowed from the East Siberian Sea to the Makarov Basin. Annual POC fluxes were 2.3 g C m-2 yr-1 and 2.0 g C m-2 yr-1 at 115 m and 335 m, respectively, on the East Siberian Sea slope and was 2.1 g C m-2 yr-1 at 325 m on the Chukchi Sea slope. Annual POC fluxes were higher on the Chukchi Sea and East Siberian Sea slopes than in Arctic basins, lower than on Arctic shelves, and generally similar to those on western Arctic slopes.